A Data‐Driven Fault Location Method in Distribution Network Based on PMU Data. Issue 3 (26th November 2021) - Fang, Jian; Wang, Hongbin; Yang, Fan; Wang, Yong; Yin, Kuang; He, Jiaxing; Lin, Xiang
Abstract: As an important part in the power systems, the status of the distribution network affects the safety, reliability, and economy of the whole power supply. When a fault occurs in the distribution network, it is of great significance to accurately and quickly locate the fault. At present, a cost‐effective synchronous phase measurement unit (PMU) device has been developed for the monitoring of the distribution network, which has opened up a new path for fault location in the distribution network. In this paper, the fuzzy clustering algorithm is used to judge the fault section, and the multiple fault information is extracted for fusion, so that the fault characteristic index can highlight the fault information. Then a new method based on multi‐terminal PMU data to realize the fault location of the distribution network is proposed. This method realizes fault location through the relationship between multiple fault indexes, and the simulation verification of PSCAD/EMTDC shows the accuracy and effectiveness of the method. © 2021 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.